2014
DOI: 10.1080/10962247.2014.990117
|View full text |Cite
|
Sign up to set email alerts
|

A study of the impact of moist-heat and dry-heat treatment processes on hazardous trace elements migration in food waste

Abstract: Using laboratory experiments, the authors investigated the impact of dry-heat and moist-heat treatment processes on hazardous trace elements (As, Hg, Cd, Cr, and Pb) in food waste and explored their distribution patterns for three waste components: oil, aqueous, and solid components. The results indicated that an insignificant reduction of hazardous trace elements in heat-treated waste-0.61-14.29% after moist-heat treatment and 4.53-12.25% after dry-heat treatment-and a significant reduction in hazardous trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…The cross-validated R 2 of the instrumental variable predicting PM 2.5 was 0.180, little changed from the R 2 in the training data (0.189). Although low, this is consistent with the fact that most of the PM 2.5 in Boston is transported rather than locally emitted, and with PM having other important sources of variation besides PBL and wind speed (Masri et al 2015). Overfitting was avoided because the tuning parameters of the model calibrating the instrument to PM 2.5 were chosen by cross-validation, and because the SVM uses a ridge penalty, where a penalty term is added to the cost function proportional to the sum of the square of the regression coefficients.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The cross-validated R 2 of the instrumental variable predicting PM 2.5 was 0.180, little changed from the R 2 in the training data (0.189). Although low, this is consistent with the fact that most of the PM 2.5 in Boston is transported rather than locally emitted, and with PM having other important sources of variation besides PBL and wind speed (Masri et al 2015). Overfitting was avoided because the tuning parameters of the model calibrating the instrument to PM 2.5 were chosen by cross-validation, and because the SVM uses a ridge penalty, where a penalty term is added to the cost function proportional to the sum of the square of the regression coefficients.…”
Section: Resultssupporting
confidence: 74%
“…Local air pollution in Boston has multiple sources, including traffic, combustion of fuel oil and residual oil for heating, and wood burning (Masri et al 2015). Traffic pollution has fallen because of reduced U.S. EPA emission standards on vehicles, low-sulfur diesel oil requirements, the retrofit of particle filters onto buses, and the introduction of compressed natural gas buses for part of the fleet (Masri et al 2015; U.S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chinese medicinal herbal residue can be a potential bulking agent/co-substrate, and Chinese medicinal herbal residue-born active ingredients are the main cause of inhibition (Zhou et al, 2016). Chen et al (2015) reported that heat treatment process did not significantly reduce the concentration of hazardous trace elements in food waste, but the separation process for solid and aqueous components, such as centrifugal dehydration, could reduce the risk considerably; they have concluded that combined with the separation technology for solid and liquid components, dry-heat treatment is superior to moist-heat treatment on the removal of external water-soluble ionic hazardous trace elements. The most important points challenging areas that represent opportunities for stakeholders to look into in China are, put in place suitable economic incentives to encourage restaurants to get more involved in the formal system, create a comprehensive regulation system to benefit all relevant stakeholders by clearly defining their respective roles and responsibilities, which is necessary for the proper functioning of the whole system, foster the development of companies specializing in different waste treatment technologies, which is a growing trend that will help achieve higher treatment efficiency at a lower cost, support and incentivize the development of a market which closes the loop and redeploys these wastes as new resources.…”
Section: Urban Food Waste Compostingmentioning
confidence: 99%